Level of physical activity and eating behavior: Risk factors associated with sedentariness among employees of a company in the city of Kinshasa province - Godefroid Kusuayi; Ekisawa Constant Kiama (Turkish Journal of Kinesiology, 2018)
The objective is to determine the level of physical activity, eating behavior and risk factors associated with sedentariness among employees of the Multimodal Freight Management Office of Kinshasa (OGEFREM, acronym). Cross-sectional study of the 210 employees, of which 119 (56.7%) men and 91 (43.3%) women, aged 18 to 59 years were randomly selected. The level of physical activity was measured by the International Physical Activity Questionnaire (IPAQ) and the eating behavior by Three-Factor Eating Questionnaire (TFEQ-R 18). The Student's T test and Chi-square test were used to compare the variables according to level of physical activity and socio-professional status. Logistic regression was used to identify independent determinants of physical inactivity and sedentary behavior. Of the 210 questionnaires collected, 56.7% of men and 43.3% of women show that 59.5% of the study population has a low level of physical activity and 58.5% a cognitive restriction. The average values of the following parameters: Weight, BMI, Waist circumference, systolic blood pressure, diastolic blood pressure, mean arterial pressure, pulsed pressure, blood glucose, total cholesterol, triglyceride, total body fat , visceral fat and lean mass are respectively 85 ± 9.7 kg, 32.6 ± 2.9 kg/m2, 99 ± 13.0 cm, 135.6 ± 17.0 mmHg, 92.1 ± 14.5 mmHg, 106.6 ± 14.3 mmHg, 43.5 ± 12.0 mmHg, 129 ± 23.9 mg / dl, 228 ± 18.7 mg / dl, 169 ± 19.5 mg / dl, 39.7 ± 10.8%, 8 ± 8.9% and 28.9 ± 9.4%. The probability of having a low level of physical activity and sedentary behavior was 5 times higher among employees spending more than three hours of time sitting on the computer (OR aj = 5.188 95% CI (1.389-7.318), p = 0.006), 3 times higher among employees over three hours of time sitting in front of the television (OR aj = 3.042 95% CI (1.155-8.012), p = 0.02), 3 times higher among employees who spent more than three hours of reading time (OR aj = 3.456 95% CI (1.294-5.677), p = 0.006 and with cognitive dietary restriction (OR aj = 3.188 95% CI (1.389-7.318) , p = 0.006), cognitive dietary restriction (OR = 3.188 95% CI (1.389-7.318), p = 0.006) and also 3 times higher among employees with high socio-occupational status (OR aj = 3.57 95% CI (1.77-6.68), p <0.015). The employees of the Multimodal Freight Management Office of Kinshasa have a low level of physical activity and a cognitive food restriction. Time spent more than three hours of time on the computer increases the risk of becoming inactive and sedentary 5 times. On the other hand, the time spent more than three hours watching television and cognitive restriction as well as the high socio-professional status increases it three times and is positively associated with morphological, physiological, lipid profiles and body composition. In contrast, they are associated with a decrease in muscle mass and high density lipoprotein.